Performance Reviewed from Occupational Safety and Health (K3), Load, Stress and Work Experience - David Karta Sasmita; Istiatin; Sudarwati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research aims to determine and explain the influence of Occupational Safety and Health (OSH), Workload, Stress, and Work Experience on the Performance of Belitung Power Plant Employees. This type of research is a quantitative research type. This research was conducted at the Belitung Power Plant. The research was conducted over a period of two months, specifically from November to December 2024. The population used in this study consists of 73 employees at the Belitung Power Plant. In this study, the sampling technique used is nonprobability sampling with the technique taken being saturated sampling (census). The researcher chose the sample using the saturated sampling technique because the population size is relatively small, so the sample used in this study consists of 73 people. Primary data in this study comes from workers' responses in the form of questionnaires about performance, K3 (Occupational Health and Safety), workload and work stress, as well as work experience. The instrument used in this study is a questionnaire with an ordinal measurement scale, which assigns values or scores to the answers obtained from the list of questions, ranging from the lowest to the highest questions. Each item question on these variables uses a measurement scale within the score range of 1 (one) to 4 (four); these scores are differentiating and ranking. This study uses multiple linear regression with the aid of SPSS 24 software. The research results show that Occupational Safety and Health (OSH), Workload, Stress, and Work Experience have an impact on the Performance of PLTU Belitung Employees by 61.9%, while the remaining 38.1% is explained by other variables not included in this study. The recommendation from this study is that PLTU employees can improve Occupational Safety and Health (OSH), Workload, Stress, and Work Experience to achieve optimal performance results for PLTU Belitung. Keywords: Performance, Occupational Safety and Health (OSH), Workload, Stress, and Work Experience, PLTU Employees